2020
DOI: 10.3390/su12198258
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Education and Environmental Worldviews: Shifting a Paradigm

Abstract: Higher education institutions are tasked with education for sustainable development, of which the environment is a central pillar. Understanding the demographic factors that influence the establishment of environmental worldviews allows educators to better contextualize sustainability content and discussion. Identifying pedagogies capable of creating learning spaces within which worldviews can shift offers similar opportunities. Using a quasi-experimental design and model building, this study identifies import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Anthropocentric worldviews arguably cultivate the exploitation of the environment for human gain regardless of the sustainability of this exploitation. In order to change this worldview and foster environmentally responsible behaviour, it has been argued that society needs to improve environmental literacy, which in turn will shift people's beliefs or value systems as they relate to the environment (Woodworth, et al, 2011;Ling, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anthropocentric worldviews arguably cultivate the exploitation of the environment for human gain regardless of the sustainability of this exploitation. In order to change this worldview and foster environmentally responsible behaviour, it has been argued that society needs to improve environmental literacy, which in turn will shift people's beliefs or value systems as they relate to the environment (Woodworth, et al, 2011;Ling, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even more effective at achieving sustainabilityrelated outcomes are the programs that specifically focus on issues of the environment and sustainability [3,14,15]. Several studies have demonstrated that learning outcomes for pro-environmental behaviors are much more significant on sustainability-focused ETPs versus other ETPs [16,17].…”
Section: Brief Review Of Educational Travel Programsmentioning
confidence: 99%
“…Dvorak and others engaged their students in developing their own personal carbon offsets that derive from lifestyle changes rather than a third-party purchase. Ling and others [16] use "socio-scientific issues" in their programs that engage students with local stakeholders to debate and develop solutions.…”
Section: Etp Impacts On Host Destinationsmentioning
confidence: 99%
“…There are many studies about the effectiveness of stand-alone sustainability courses [17][18][19][20][21] or general university studies oriented partly towards sustainability [20,[22][23][24][25]. Some previous studies showed that even stand-alone sustainability courses [21,26] and education oriented for sustainability [22][23][24][25] are only partially successful in changing the attitudes of students.…”
Section: Introductionmentioning
confidence: 99%